4‐Cyano‐α‐methyl‐l‐phenylalanine as a Spectroscopic Marker for the Investigation of PeptaibioticMembrane Interactions. Issue 4 (April 2015) - De Zotti, Marta; Bobone, Sara; Bortolotti, Annalisa; Longo, Edoardo; Biondi, Barbara; Peggion, Cristina; Formaggio, Fernando; Toniolo, Claudio; Dalla Bona, Andrea; Kaptein, Bernard; Stella, Lorenzo
Abstract Two analogs of the ten‐amino acid residue, membrane‐active lipopeptaibiotic trichogin GA IV, mono‐labeled with 4‐cyano‐α‐methyl‐L‐phenylalanine, a potentially useful fluorescence and IR absorption probe of the local microenvironment, were synthesized by the solid‐phase methodology and conformationally characterized. The single modification was incorporated either at the N‐terminus (position 1) or near the C‐terminus (position 8) of the peptide main chain. In both cases, the replaced amino acid was the equally helicogenic α‐aminoisobutyric acid (Aib) residue. We performed a solution conformational analysis by use of FT‐IR absorption, CD, and 2D‐NMR spectroscopies. The results indicate that both labeled analogs essentially maintain the overall helical propensity of the naturally occurring lipopeptaibiotic. Peptidemembrane interactions were assessed by fluorescence and ATR‐IR absorption techniques. Analogies and differences between the two peptides were highlighted. Taken together, our data confirm literature results that some of the spectroscopic parameters of the 4‐cyanobenzyl chromophore are sensitive markers of the local microenvironment.